Principal Leadership in Improving Teacher Professionalism in Terms of: Leadership Models and Strategies - Septiara Yolanda; Sufyarma M; Sulastri Sulastri (International Journal of Educational Dynamics, 2022)
Principal leadership has a major role in increasing teacher professionalism. This study aims to describe qualitatively the principal's leadership in improving teacher professionalism in terms of leadership models and strategies. This study used the systematic literature review method to answer the research variable question, namely how school principal leadership improves teacher professionalism in terms of leadership models and strategies. Researchers limit the year of publication of the references used from the last 6 years. The stages carried out in the study of this research literature were; 1) formulating research questions; 2) conducting a literature search; 3) screening research articles; 4) performing analysis and synthesis on qualitative findings; 5) performing quality control; and 6) prepare a final report. Based on the literature review conducted, it was found that teacher professionalism can be increased through the use of a democratic leadership model and the strategies used are a) involving teachers in MGMP/KKG activities; b) carrying out academic supervision activities for teachers; and c) providing education and training required by teachers.